Time‐Varying World Market Integration - BEKAERT, GEERT; HARVEY, CAMPBELL R. (Journal of Finance, 1995)
ABSTRACT We propose a measure of capital market integration arising from a conditional regime‐switching model. Our measure allows us to describe expected returns in countries that are segmented from world capital markets in one part of the sample and become integrated later in the sample. We find that a number of emerging markets exhibit time‐varying integration. Some markets appear more integrated than one might expect based on prior knowledge of investment restrictions. Other markets appear segmented even though foreigners have relatively free access to their capital markets. While there is a perception that world capital markets have become more integrated, our country‐specific investigation suggests that this is not always the case.